(3NQjOI GdYLGFH haQjOI GdZQGFHs - (3YeQ Hf eXaQ Hf YeQ H eMeO GHf CHj GdahGQS, CHh MaU, Rjf GdOjf GHf GdhQOj GdeYQj GdcfOj,J (B749 (3g` s ((3CMeO Hf eMeO Hf CHj GdbGSe GdcTJHGf s)
(3ChdgG (B:s
(3bd dGjYde ef ai GdSehGJ hGdCQV GdZjH EdG Gddg hHYO , aEf NGdb GdNdb hGdHQjI , hef dg GdEQGOI hGdeTjI , bO ejR Gdedhc hGdOYGI Yf ef Ohfge ef GdQYjI s
(3BNQgG (B:s
(3hgPg NGJeI GdCQLhRI heG MhJ ef Mce ZRjQ Je GdcJGH HMeO Gddg s
(3GdfSNI HgG MhGTs
(3HgG HYV GdJbUas
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf HGdMeQI s
(3hGdQShe HGdOGNd edhfI HCcKQ ef dhf s
(3bQf GdfSN (B:s
Keywords: (3GdJGQjNs